Jenufa lobulosa sp. nov. (Chlorophyceae, Chlorophyta), a new epilithic, terrestrial species described from China. Issue 1 (1st January 2018) - Song, Huiyin; Li, Shuyin; Liu, Xudong; Wang, Qinghua; Zhu, Huan; Liu, Guoxiang; Hu, Zhengyu
Abstract: Unicellular coccoid green algae are characterised by a high cryptic diversity, but such diversity is still poorly known, especially in terrestrial environments. The genus Jenufa, first described in 2011 from terrestrial habitats, currently includes three species: J. perforata, J. minuta and J. aeroterrestrica . We describe a new species, Jenufa lobulosa sp. nov . The type strain FACHB-2128 was isolated from sandstone surfaces in Nanning, Guangxi Province, a subtropical area in southwestern China, and the cultured material was examined using light and electron microscopy. It shared representative features of the genus: a parietal perforated chloroplast with several lobes, no pyrenoids, and asexual reproduction via autospores. However, J. lobulosa differed from congeners in the mean size of its vegetative cells and autosporangia, the number of autospores and cell wall thickness. Phylogenetic analyses of 18S rDNA and rbc L sequences showed that strain FACHB-2128 belonged to the Jenufa clade of the Chlorophyceae, forming an independent lineage and differing from any known species. The position of strain FACHB-2128 within Jenufa was also supported by ITS2 rDNA sequences.